Release kinetics of thymol and antibacterial properties of starch films containing CNP-T and free thymol - Ahmad Shapi, Ruzanna; Othman, Siti Hajar (Institute of Nanoscience and Nanotechnology (ION2), 2024)
Millions of tons of food are wasted globally every year, usually due to inadequate storage and handling practices. This not only leads to food insecurity but also emits greenhouse gases that are harmful to the environment. Plastics are frequently used for food storage, but their non-biodegradable nature is also harmful to the environment. Addressing these challenges requires sustainable packaging alternatives with active attributes such as antibacterial properties that can prolong the food shelf-life. Starchbased films incorporated with chitosan nanoparticles encapsulating thymol (CNP-T) and free thymol were produced via solvent casting. The release kinetics of thymol from films into food simulants were investigated. The antibacterial activity of films on Staphylococcus aureus and Salmonella typhimurium was also investigated via disc diffusion analysis. The results indicate that the starch films containing CNP-T exhibited a significantly improved controlled release profile of thymol compared to that of free thymol. The films incorporated with CNP-T show a larger inhibition zone of all bacteria than those incorporated with free thymol. The starch-based films with CNP-T present a promising approach to maintaining food quality while mitigating the environmental impact. This research contributes to the development of sustainable solutions for addressing global challenges in food.